No association of the variant rs11887120 in DNMT3A with cognitive decline in individuals with mild cognitive impairment. (May 2016) - Bey, Katharina; Wolfsgruber, Steffen; Karaca, Ilker; Wagner, Holger; Lardenoije, Roy; Becker, Julian; Milz, Esther; Kornhuber, Johannes; Peters, Oliver; Frölich, Lutz; Hüll, Michael; Rüther, Eckart; et al.
Alterations in DNA methylation have been associated with cognitive decline and Alzheimer's disease. A recent study of mild cognitive impairment (MCI) reported a significant association between annual decline in cognitive function and the rs11887120 SNP located in DNMT3A, a gene implicated in DNA methylation. Here, we aimed to replicate this finding in two independent MCI cohorts (n = 1024); however, no significant association was observed in either cohort or the pooled dataset. In stratified analyses for conversion to Alzheimer's disease status, no association between rs11887120 and cognitive decline was observed in either converters or nonconverters. In conclusion, our analyses provide no support for the hypothesis that genetic variants in DNMT3A are implicated in cognitive performance decline in individuals with MCI.